Kekerasan Dalam Pendidikan (Studi Analitik Perspektif Pemikiran Ibnu Khaldun Dalam Kitab Muqodimah) - Aini Nur Ma'rifah (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2020)
This study aims to describe violence in education in the perspective of Ibn Khaldun. This research uses library research with primary and secondary sources of literature study data collection techniques. The results of research that Ibn Khaldun's solution in this case as explained in his book that it is better to treat students as people who have full freedom of themselves, the attitude of a teacher to students and the attitude of parents to their children are not arbitrary in educating, and so that make a student comfortable in the conditions and learning situations.